Incidental Findings in Digital Panoramic Radiography of Patients Referred to Mashhad Dental School - Mahrokh Imanimoghaddam; Elaheh Tohidi; Azam Ahmadian Yazdi; Ehsan Nikbakhsh; fereshteh goudarzi (Journal of Kerman University of Medical Sciences, 2021)
Background:Panoramic radiographs are among diagnostic tools used by dentists. Because of the relatively large area covered by panoramic radiographs, incidental findings are possible. This study aimed to evaluate the incidental findings in digital panoramic radiographs of patients referred to the Oral and Maxillofacial Radiology Department of Mashhad Dental School. Methods:In this cross-sectional study, panoramic radiographs of 1987 patients over one year were evaluated, and any finding that was not related to the reason of panoramic radiography request was recorded as an incidental finding. These findings were grouped into five categories: intraosseous findings, dental abnormalities, soft tissue calcifications, maxillary sinus findings, and TMJ findings. The obtained data were analyzed using descriptive statistics and through SPSS18.0. Results: A total of 3990 findings in 1987 patients, including 795 men and 1192 women aged 4 to 84 years old, were identified. The overall rate of incidental findings was 85%. The highest rate of incidental findings was related to intraosseous findings (53.8%), followed by dental anomalies (34.7%), soft tissue calcifications (21.2%), maxillary sinus (17.3%), and TMJ findings (3.2%). The most prevalent intraosseous incidental finding was rarefying osteitis. The most common dental abnormalities were impaction and missing. Half of the soft tissue calcifications were elongated calcified styloid ligament. The most common sinus and TMJ incidental findings were mucosal thickenings and articular eminence pneumatization, respectively. Conclusions:Incidental findings in panoramic radiographs are common. Although most of the findings do not require treatment, early diagnosis of some of these findings is beneficial in preventing subsequent complications in patients.